The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acssuschemeng.0c04345
|View full text |Cite
|
Sign up to set email alerts
|

Dual Colorimetric and Ratiometric Fluorescent Responses for the Determination of Glutathione Based on Fluorescence Quenching and Oxidase-Like Activity of MnO2 Nanosheets

Abstract: A dual colorimetric and ratiometric fluorescent assay is constructed for the detection of glutathione (GSH) based on MnO 2 nanosheets (MnO 2 NS). Amplex Red (AR) and curcumin (CUR) fluorescence-pairing probes have opposite responses to MnO 2 NS with fluorescence quenching and oxidaselike property. MnO 2 nanosheets can largely quench the fluorescence of curcumin. However, the fluorescence of oxidized AR (oxAR) was obviously raised via the catalytic oxidation reaction of no fluorescent AR. The color of the solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…For Au NCs@a-MnO 2 -60 NSs, two peaks at 84.0 and 87.7 eV in Au 4f spectrum were Au 4f 7/2 and Au 4f 5/2 of Au 0 , respectively (Figure a) . The Mn 2p doublets at 642.1 and 653.9 eV were Mn 2p 3/2 and Mn 2p 1/2 of Mn 4+ , respectively, with the satellite peak of Mn 4+ at 644.6 eV (Figure b). , In the O 1s XPS spectrum, the binding energies at 529.7 and 532.9 eV were the metal–O bonds and hydroxide species at the product’s surface, respectively, whereas the peak at 531.3 eV corresponded to defect sites with low oxygen coordination (Figure c). Notably, the binding energies of Au 4f in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs shifted to lower values than those of Au NCs (Figure d), whereas the binding energies of Mn 2p in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs shifted to higher values compared to those in a-MnO 2 NSs and c-MnO 2 NSs (Figure e). These results demonstrated that the electrons were transferred from Mn to Au in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs, making Au NCs core electron-rich and MnO 2 NSs shell electron-deficient.…”
Section: Resultsmentioning
confidence: 92%
“…For Au NCs@a-MnO 2 -60 NSs, two peaks at 84.0 and 87.7 eV in Au 4f spectrum were Au 4f 7/2 and Au 4f 5/2 of Au 0 , respectively (Figure a) . The Mn 2p doublets at 642.1 and 653.9 eV were Mn 2p 3/2 and Mn 2p 1/2 of Mn 4+ , respectively, with the satellite peak of Mn 4+ at 644.6 eV (Figure b). , In the O 1s XPS spectrum, the binding energies at 529.7 and 532.9 eV were the metal–O bonds and hydroxide species at the product’s surface, respectively, whereas the peak at 531.3 eV corresponded to defect sites with low oxygen coordination (Figure c). Notably, the binding energies of Au 4f in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs shifted to lower values than those of Au NCs (Figure d), whereas the binding energies of Mn 2p in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs shifted to higher values compared to those in a-MnO 2 NSs and c-MnO 2 NSs (Figure e). These results demonstrated that the electrons were transferred from Mn to Au in Au NCs@a-MnO 2 -60 NSs and Au NCs@c-MnO 2 NSs, making Au NCs core electron-rich and MnO 2 NSs shell electron-deficient.…”
Section: Resultsmentioning
confidence: 92%
“…24 Moreover, the strategy of using the nanoprobes such as AuNCs and fluorescence polydopamine nanoparticles was relatively complex and their fluorescence properties may be greatly affected by the microenvironment. 25 Another unique property of MnO 2 nanosheets or nanoflakes is their oxidase (OXD)-or peroxidase-like activity, which has also attracted much attention. 26,27 The mimicking properties can be used in construction of colorimetric sensors for the rapid qualitative analysis of various substrates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26,27 The mimicking properties can be used in construction of colorimetric sensors for the rapid qualitative analysis of various substrates. 28,29 Compared with the colorimetric sensing, fluorescence analysis is more sensitive. Meanwhile, in situ formation of fluorescence species as the signal output based on the nanozyme activity of MnO 2 may be more convenient because there is no need to synthesize fluorescent nanoprobes with higher purity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations